2015
DOI: 10.1007/s00406-015-0582-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar contributions to neurological soft signs in healthy young adults

Abstract: Neurological soft signs (NSS) are frequently found in psychiatric disorders of significant neurodevelopmental origin, e.g., in patients with schizophrenia and autism. Yet NSS are also present in healthy individuals suggesting a neurodevelopmental signature of motor function, probably as a continuum between health and disease. So far, little is known about the neural mechanisms underlying these motor phenomena in healthy persons, and it is even less known whether the cerebellum contributes to NSS expression. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…Activation of the pre‐ and postcentral gyri, the temporal gyrus, the insula and the cerebellar areas during the FEP motor sequence, and activation of the precentral, superior temporal and fusiform gyri during audiovisual integration were consistent with evidence from previous structural MRI studies of complex motor sequencing in healthy individuals (Dazzan et al, ; Hirjak et al, ; Thomann et al, ). These findings suggest that the FEP and AVI tasks can capture the complex motor sequencing and sensory integration functions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Activation of the pre‐ and postcentral gyri, the temporal gyrus, the insula and the cerebellar areas during the FEP motor sequence, and activation of the precentral, superior temporal and fusiform gyri during audiovisual integration were consistent with evidence from previous structural MRI studies of complex motor sequencing in healthy individuals (Dazzan et al, ; Hirjak et al, ; Thomann et al, ). These findings suggest that the FEP and AVI tasks can capture the complex motor sequencing and sensory integration functions.…”
Section: Discussionsupporting
confidence: 87%
“…Although many studies have focused on these impairments in psychiatric disorders, their underlying neural mechanism and whether these impairments are heritable is not known. Empirical evidence has demonstrated that the grey matter volumes of the pre‐ and postcentral gyri, and the frontal and temporal lobes were associated with impairments in complex motor sequencing, sensory integration, or both in healthy individuals (Dazzan et al, ; Hirjak, Thomann, Kubera, Stieltjes, & Wolf, ; Hirjak, Wolf, Kubera, Stieltjes, & Thomann, ; Thomann, Hirjak, Kubera, Stieltjes, & Wolf, ). While the evidence for the association between complex motor sequencing/sensory integration and subcortical volumes was found in patients with schizophrenia, similar associations have not been found in healthy controls (Bottmer et al, ; Dazzan et al, ; Heuser et al, 2011; Ho, Mola, & Andreasen, ; Kong, Bachmann, Thomann, Essig, & Schroder, ; Mouchet‐Mages et al, ; Thomann et al, ; Venkatasubramanian, Jayakumar, Gangadhar, & Keshavan, ).…”
Section: Introductionmentioning
confidence: 99%
“…We chose to investigate neural correlates of NSS with restingstate fMRI because functional brain alterations underlying NSS in SSD are intrinsic and therefore they may be better examined without the confounders of a non-ecological setting (e.g., scanner and paradigm) and the patient's motivational bias. Previous MRI studies have confirmed this notion and successfully used resting-state fMRI (e.g., regional homogeneity (ReHo) to study NSS in healthy individuals (Hirjak, Thomann, Kubera, Stieltjes, & Wolf, 2016;. ReHo is a voxel-based measure of focal connectivity that evaluates the synchronicity of the time series between a given voxel and each of its 26 neighboring voxels (Zang, Jiang, Lu, He, & Tian, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…In patients with schizophrenia, a dysfunction of the cerebellum has been related to neurological soft signs. Hirjak et al [4] performed a structural and resting-state magnetic resonance imaging (MRI) investigation in 37 healthy young adults symptoms can be described by a reverse U-shaped curve. Neurocognitive assessments show that schizophrenia patients have deficits in Theory of Mind (ToM), which refers to the capacity to make inferences about one's own and others' thoughts and intentions.…”
mentioning
confidence: 99%